A Systematic Literature Review on Optimization Techniques for Quantum Computing Compilers - Rocha, Camilla Vitoria Bueno da; Santos, Ana Luiza Diniz; Souza, Matheus Alcântara (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais Estendidos do XXIV Simpósio em Sistemas Computacionais de Alto Desempenho, 2023)
The rapid development of Quantum Computing (QC) as a promising computing paradigm has garnered significant attention for its ability to harness quantum mechanical properties for computation. With classical computing facing limitations outlined by Moore’s Law, QC emerges as a potential alternative for tackling complex computational problems. Yet, to unlock its full potential, robust and optimized compilers are pivotal, especially in addressing challenges posed by circuits with numerous qubits. In this systematic literature review, we analyze 18 articles to identify proposed optimizations for quantum compilers, exploring their applications, performance impacts, and emerging trends. Our primary goal is to offer valuable insights into the recent advancements and challenges in QC compiler optimizations. This will be achieved through the clustering of optimization groups, ultimately facilitating further progress in the development of highly optimized quantum algorithms and circuits.